INNOVATIVE POTENTIAL FOR THE DEVELOPMENT OF PERMANENT MAKEUP BASED ON TECHNIQUE IMPROVEMENT AND CLIENT SUPPORT - Yakovenko, Inna (SWorldJournal, 2025)
The article analyzes the innovative potential for the development of permanent makeup through the refinement of application techniques and the implementation of modern client support strategies. The aim of the study is to identify and systematize technolo